2016
DOI: 10.1007/s12033-016-9960-z
|View full text |Cite
|
Sign up to set email alerts
|

Engineered β-Lactoglobulin Produced in E. coli: Purification, Biophysical and Structural Characterisation

Abstract: Functional recombinant bovine β-lactoglobulin has been produced by expression in E. coli using an engineered protein gene and purified to homogeneity by applying a new protocol. Mutations L1A/I2S introduced into the protein sequence greatly facilitate in vivo cleavage of the N-terminal methionine, allowing correctly folded and soluble protein suitable for biochemical, biophysical and structural studies to be obtained. The use of gel filtration on Sephadex G75 at the last purification step enables protein witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 50 publications
3
12
0
Order By: Relevance
“…The CD spectra of FAF and FAW (Supplementary Fig. S2) were compared with the spectrum of the WT recombinant protein, which is identical to that of the natural (native) protein (Loch et al, 2016). The FAF spectrum is consistent with the spectra recorded for other lactoglobulin mutants (Loch et al, 2018), while for FAW a significant increase of the signal is observed in the entire spectrum range.…”
Section: Overall Fold and Thermal Stability Of The Blg Mutantssupporting
confidence: 56%
See 2 more Smart Citations
“…The CD spectra of FAF and FAW (Supplementary Fig. S2) were compared with the spectrum of the WT recombinant protein, which is identical to that of the natural (native) protein (Loch et al, 2016). The FAF spectrum is consistent with the spectra recorded for other lactoglobulin mutants (Loch et al, 2018), while for FAW a significant increase of the signal is observed in the entire spectrum range.…”
Section: Overall Fold and Thermal Stability Of The Blg Mutantssupporting
confidence: 56%
“…The presence of mutations was confirmed by DNA sequencing (Genomed S.A., Poland). The genes for both of the new variants, I56F/L39A/M107F (FAF) and I56F/L39A/M107W (FAW), carried the N-terminal L1A/ I2S substitutions (Loch et al, 2016). The FAF and FAW proteins were expressed and purified according to the previously published protocol #2 (Loch et al, 2016).…”
Section: Mutagenesis Protein Expression and Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…α-2 may thus be required for stabilization of the dimeric state. α-3 (residues 113–116 in the GH loop) was found in the present pH 4.0 crystal structure and in the crystal structure determined at pH 6.5, but lacking in all other reported crystal , ,, and NMR structures, , and hence is not well conserved (Table S1). α-4 (residues 153–157 in the C-terminal loop) was similar in the present pH 4.0 and crystal structures at pH 5.2 (2AKQ), pH 6.2 (3BLG), and pH 8.2 (2BLG), one residue longer than in structures at pH 2.0 (1CJ5) and 6.5–7.3 (1BSO, 1BSQ, and 1BEB), ,, one residue shorter than in the NMR structure at pH 2.6 (1DV9) (Table S1), and lacking in the crystal structure at pH 8.5.…”
Section: Resultsmentioning
confidence: 49%
“…Using PyMOL, the secondary structure elements in the present crystal structure were compared with earlier crystal structures covering the pH range 5.2–8.5; 2AKQ (pH 5.2); 3BLG (pH 6.2); 1BEB (pH 6.5); 1BSQ (pH 7.1); 1BSO (pH 7.3); 2Q2M (pH 7.4); 2BLG (pH 8.2); and 5HTE (pH 8.5) as well as with two NMR structures: 1CJ5 (pH 2.0) and 1DV9 (pH 2.6) (Table S1). Helix α-1 (residues 12–15 in the N-terminal loop) is several residues longer in some of these other BLGA structures and not well conserved in the lipocalin family. , α-2 (residues 29–33 in the AB loop) in previously reported structures was formed by residues 29–32 and is together with strand I situated at the dimer interface and lacking in the NMR monomer structures determined at pH 2.0 (1CJ5) and at pH 2.6 (1DV9) .…”
Section: Resultsmentioning
confidence: 99%